2022
DOI: 10.2196/39596
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Experiences After Implementation of an Organization-Wide Electronic Medical Record: Qualitative Descriptive Study

Abstract: Background Reports on the impact of electronic medical record (EMR) systems on clinicians are mixed. Currently, nurses’ experiences of adopting a large-scale, multisite EMR system have not been investigated. Nurses are the largest health care workforce; therefore, the impact of EMR implementation must be investigated and understood to ensure that patient care quality, changes to nurses’ work, and nurses themselves are not negatively impacted. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(52 citation statements)
references
References 44 publications
0
45
0
7
Order By: Relevance
“…There were no contradictory or conflicting programme theories in the included articles to support dismissal of initial programme theories one and four. These initial programme theories were developed based on evidence from previous work and were therefore retained in their original form (Jagosh, 2020; Jedwab et al, 2019; Jedwab, Hutchinson, et al, 2021; Jedwab, Manias, et al, 2022; Wong et al, 2013). Assessment of causal inferences derived from included articles was heuristically operationalised by the research team by examining articles for causal inferences related to findings reported by the authors and discussing the applicability and relevance of findings and causality reported in articles (Jagosh, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no contradictory or conflicting programme theories in the included articles to support dismissal of initial programme theories one and four. These initial programme theories were developed based on evidence from previous work and were therefore retained in their original form (Jagosh, 2020; Jedwab et al, 2019; Jedwab, Hutchinson, et al, 2021; Jedwab, Manias, et al, 2022; Wong et al, 2013). Assessment of causal inferences derived from included articles was heuristically operationalised by the research team by examining articles for causal inferences related to findings reported by the authors and discussing the applicability and relevance of findings and causality reported in articles (Jagosh, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Eight initial theories (programme theories; Appendix 1) generated from a scoping review (Jedwab et al, 2019) and findings of a large qualitative study (Jedwab, Hutchinson, et al, 2021; Jedwab, Manias, et al, 2022) were used as the basis to explore, examine and synthesise literature from a range of sources (Rycroft‐Malone et al, 2012). These initial programme theories informed the review data collection, analysis and synthesis process and were revised as the review progressed (Jagosh, 2020; Jedwab, Redley, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half (10/17,59%) of the studies reported on CDS tools, with 29% (5/17) of the studies investigating conventional CDS [ 62 , 63 , 66 , 67 , 71 ] and 29% (5/17) of the studies focusing on AI-based CDS [ 59 , 61 , 65 , 69 , 70 ]. Of the 17 studies, 6 (35%) focused on EHRs [ 58 , 60 , 64 , 68 , 73 , 74 ], whereas the remaining 1 (6%) study examined a remote patient-monitoring tool [ 72 ]. Of the 17 studies, 13 (76%) were solely based on qualitative individual semistructured interviews.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 4 studies, 2 (50%) adopted a combination of qualitative techniques, consisting of individual semistructured interviews, focus group interviews, field notes, and direct observation. Of the 17 studies, the other 2 (12%) followed a mixed methods approach [ 61 , 64 ]. They conducted qualitative individual semistructured interviews and enriched their data with quantitative surveys using the 5-point Likert scale [ 66 , 74 ].…”
Section: Resultsmentioning
confidence: 99%